PENGELOLAAN MANAJEMEN OLAHRAGA PARIWISATA DI LOKASI WISATA AIR TERJUN NYARAI - Syafrizar Syafrizar; Hermanzoni Hermanzoni (Jurnal Sporta Saintika, 2017)
One of the recreational sports that began to develop is at Air Terjun Lubuk Nyarai. Nyarai is one of the most beautiful waterfalls we found in West Sumatra. This waterfall is often termed as a fragment of Paradise in West Sumatra. This waterfall is located in Gamaran Forest, Jorong Gamaran, Korong Salibutan, Kec. Lubuk Alung, Kab. Padang Pariaman, West Sumatera. From the results of interviews from both groups that equally manage tourism services Air Terjun Lubuk Nyarai. Nyarai found some problems are as follows: the low support of government in developing recreational sports tourism potential at Air Terjun Lubuk Nyarai. Nyarai, the limitations of recreational sports facilities and infrastructure , limitations in terms of managing / management and tourism promotion Nyarai Waterfall. The solutions and outreach targets of community service activities are: 1) The lack of government support for recreational recreational tourism potential at Nyarai Waterfall, provided solutions in the form of workshops and workshops by finding the Awake Group of LA Adventure and Lubuk Nyarai Guide groups with local communities and the government in this case will be asked Padang Pariaman Tourism Office, to discuss the development of recreational sports Air Terjun Lubuk Nyarai. Nyarai, 2) Promotion and marketing tourism recreation sport at Air Terjun Lubuk Nyarai. Nyarai is not maximized, given the solution with way management management and marketing management place, The absence of guidebooks tracking track and tour guide Nyarai Waterfall, given the solution that is by making a standard book track tracking and tour guide Nyarai Waterfall. Based on the results of the activities of "IbM Air Terjun Nyarai and the discussion can be concluded the following results: 1) Increased knowledge, experience and skills of the community and the tour guide on the management of a tourist attraction especially sport tourism at Nyarai Waterfall, 2) Increased knowledge, experience and skills of the community and the youth regarding the promotion and marketing of a tourist site especially sports tourism at Nyarai Waterfall, 3) Increased skills of the community and youth about in guiding outbound and outdoor activities at Nyarai Air Terjun Lubuk Nyarai. Nyarai.